De novo transcriptome analysis of Cnidium monnieri (L.) Cuss and detection of genes related to coumarin biosynthesis - Yuanyuan Shi; Shengxiang Zhang; Daiyin Peng; Chunmiao Shan; Liqiang Zhao; Bin Wang; Jiawen Wu (PeerJ, 2020)
Cnidium monnieri (L.) Cuss (C. monnieri) is one of the most widely used traditional herbal medicines, exhibiting a wide range of pharmacological functions for treating asynodia, trichomonas vaginitis, and osphyalgia. Its important medicinal value comes from its abundance of coumarins. To identify genes involved in coumarin biosynthesis and accumulation, we analyzed transcriptome data from flower, leaf, root and stem tissues of C. monnieri. A total of 173,938 unigenes with a mean length of 1,272 bp, GC content of 38.79%, and N50 length of 2,121 bp were assembled using the Trinity program. Of these, 119,177 unigenes were annotated in public databases. We identified differentially expressed genes (DEGs) based on expression profile analysis. These DEGs exhibited higher expression levels in flower tissue than in leaf, stem or root tissues. We identified and analyzed numerous genes encoding enzymes involved in coumarin biosynthesis, and verified genes encoding key enzymes using quantitative real-time PCR. Our transcriptome data will make great contributions to research on C. monnieri and provide clues for identifying candidate genes involved in coumarin metabolic pathways.